The Origins of Hizbut Tahrir Indonesia: Global And Local Interactions - Rijal, Syamsul (Islamic Studies Review, 2022)
This article examines the resurgence and development of transnational Islamic movements in the post-reform era by analysing the case of Hizbut Tahrir Indonesia (HTI). It argues that HTI’s emergence and rapid expansion is intertwined with global and Indonesian socio-political contexts. While the global factor of the Iranian revolution of 1979 inspired the revival of Islam as a social, political, and cultural force in Muslim countries, the changing political situation in Indonesia — from authoritarianism to the reform era — supported the growth and expansion of HTI in major universities in Indonesia. Although HTI gradually grew after its arrival in 1980s, it only emerged into the public view in 2000 when it hosted the first International Caliphate Conference in Jakarta. HTI's emergence was part of a broader proliferation of Islamic radical groups, which took place following the end of the Soeharto regime in May 1998. This article discusses how this movement operated underground through preaching groups on campuses, established media operations, and organised rallies in support of a global caliphate in Indonesia. By looking at national and local levels, this study suggests that, in the newly democratic political sphere, HTI won the support of ordinary Indonesian people by engaging with national and local issues as part of efforts to achieve its agenda of establishing shari'a and a global caliphate.